The influence of elements in brand story towards customer purchase intention through narrative engagement in Indonesia - Afradyta, Sastia Roria; Maryunani, Salfitrie Roos (Journal of Innovation, Business and Entrepreneurship, 2019)
Fashion industry is one of the world's largest economies and attracts many entrepreneurs to enter this industry. In Indonesia, there are more than one million fashion businesses and the number keeps increasing that makes this industry highly competitive. In order for a business to survive, one needs to find a way to make their business stand out and a strong brand story can be the solution. In this paper, the researcher will present an adapted conceptual framework regarding the influence of four elements of brand story towards narrative engagement, brand attitude and purchase intention, specifically in Indonesian fashion brand that use traditional fabric in the products. The purpose is to determine which element from brand story that has significant influence and the result can be used as a reference for other fashion entrepreneur to build a strong brand story for their business. The data used in this research are 138 which is gathered by spreading the questionnaire through Line and Instagram. Microsoft Excel and SmartPLS are used to process the data and result is only humour has significant influence to narrative engagement, narrative engagement has significant influence to brand attitude and purchase intention, and brand attitude of the use of traditional fabric in the product hassignificant influence to purchase intention.Keywords: Brand Story, Narrative Engagement, Brand Attitude, Purchase Intention, Fashion Business